Prefrontal dysfunction in post-COVID-19 hyposmia: an EEG/fNIRS study - Clemente, Livio; La Rocca, Marianna; Quaranta, Nicola; Iannuzzi, Lucia; Vecchio, Eleonora; Brunetti, Antonio; Gentile, Eleonora; Dibattista, Michele; Lobasso, Simona; Bevilacqua, Vitoantonio; Stramaglia, Sebastiano; de Tommaso, Marina (Frontiers in Human Neuroscience, 2023)
Subtle cognitive dysfunction and mental fatigue are frequent after Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov2) infection, characterizing the so called long-Covid syndrome. The aim of this study was to correlate cognitive, neurophysiological, and olfactory function in a group of subjects experienced acute SARS-Cov2 infection with persistent hyposmia at least 12 weeks before the observation. For each participant (32 post-covid patients and 16 controls), electroencephalography (EEG) and functional near-infrared spectroscopy (fNIRS) data were acquired, using an integrated EEG–fNIRS system, during the execution of a P300 odd-ball task and a Stroop test. The Sniffing Sticks Test to assess subjects’olfactory performance was measured. The Montreal Cognitive Assessment (MoCA) and the Frontal Assessment Battery (FAB) were also administered. Post-COVID group consisted of 32 individuals (20 females and 12 males) with an average education level of 12.9 ±3.12 years, while the control group consisted of 16 individuals (10 females and 6 males) with an average education level of 14.9 ±3.2 years. There were no significant differences in gender (X2=0, p=1) and age between the two groups (age 44.81 ± 13.9 versus 36.62 ± 11.4, p 0.058). We identified a lower concentration of oxyhemoglobin (p <0.05) at the prefrontal cortical level in post Covid subjects during the execution of Stroop task, as well as a reduction of amplitude of the P3a response. Moreover, we found that post-Covid subjects performed worst at the MoCA screening test (p=.001), Sniffin’s sticks test (p<.001), and Stroop task response latency (p<.001). This study showed that post-COVID-19 patients with persistent hyposmia present mild deficits in prefrontal function, even four months after the end of the infection. These deficits, although subtle, could have long-term implications on quality of life and cognitive well-being. It is essential to continue monitoring and evaluating these patients to better understand the extent and duration of cognitive impairments associated with long COVID.